Pathways for novel magnetocaloric materials: A processing prospect. Issue 5 (27th March 2014) - Krautz, Maria; Hosko, Josef; Skokov, K.; Svec, Peter; Stoica, Mihai; Schultz, Ludwig; Eckert, Jürgen; Gutfleisch, Oliver; Waske, Anja
Abstract: Composites of two magnetocaloric components have been prepared by melt spinning. A special nozzle modification allows to separate the melts of two different materials which solidify simultaneously as rapidly quenched composite. Two materials combinations were chosen: (a) Fe‐based amorphous materials with different Cr‐contents and (b) Fe‐based alloys with different Si‐content resulting in crystalline La(Fe, Si)13 phase with large magnetocaloric effect after subsequent annealing. By melt spinning crystalline segments of several cm length and long amorphous ribbons were obtained. The magnetocaloric properties of the composites were assessed by magnetometry and direct measurements of the adiabatic temperature change. (© 2014 WILEY‐VCH Verlag GmbH & Co. KGaA, Weinheim)